Epidemiological and clinical characteristics of patients with Basal cell carcinoma (BCC) in the eyelid - Isjanovski, Igor; Isjanovski, Viktor; Stavrikj, Dejan; Isjanovska, Rozalinda; Orovchanec, Nikola (My University, 2011)
Itroduction:BCC is a malignant cutaneous neoplasm capable of extensive tissue destruction. BCC rarely metastasises. BCC is the most common skin cancer of the eyelid, accounting for 80-89% of cases Aim: To describe the epidemiological and clinical characteristics of patients with eyelid BCC. Methods: Epidemiological data of BCC in the eyelid has been collecting from Clinic of ophthalmology-Skopje. The data of all cases of Macedonian residents with eyelid BCC diagnosed from 2007 to 2009y. were retrieved for analysis. We analyzed sex and age distribution, localization, dimension and type of BCC in the eyelids Results: BCC is slightly more common in males than in females with a male-to-female ratio of 2:1. more of them are male-67% and female-33%, differences was statistical significant-p<0,05. There were not statistical significant association(p>0,05) between gender and BCC. The percents of BCC increase with advancing age and tend to occur in the seventh decade of life. The mean age is 68,03±10,8y. Approximately 72% of cases of BCC occur in the patients aged over 60y. There were statistically significant differences between urban (32%) and rural (68%) populations. The most frequent histological subtype was nodular(52%), followed by superficial(17%) and 71% belongs to the squamous cell, followed by kerotic cells-13%.Localisation of BCC was mainly on the lower eyelid-49%, and the medial canthal region-27%, but involved the right and left sides with equal frequency.. In 59% of the cases, the diameter of the lesion was smaller than 11mm. Conclusion: These expanded epidemiological characteristics may serve to provide a foundation to monitor future disease patterns and to promote further research into the a etiology of these cancers. All patients with lesions should be advised of the risk of recurrent or new BCC , a biopsy of all suspicious lesions followed by complete surgical excision with microscopic monitoring of the margins has the best chance for cure..
Keywords: epidemiological characteristics; clinical characteristics; BCC; eyelids